TAX MODERNIZATION IN INDONESIA: STUDY OF ABU YUSUF’S THINKING ON TAXATION IN THE BOOK OF AL-KHARAJ - A Amrin; K Khairusoalihin; M Muthoifin (Universitas Muhammadiyah Surakarta, 2022)
tax for a country is one of the main income in the country so that the tax funds collected will have a positive impact on the population of that country, the purpose of this research is to provide education to Muslims that the tax culture that has developed in Indonesia at this time has existed since the classical Islamic era. namely in the time of Abu Yusuf, the type of research carried out by researchers in this paper was a qualitative method using a library method (library) which was reviewed from historical, books and previous research results, in research, it has been suggested that there is a modernization system in taxation in Indonesia where In the era of Abu Yusuf, taxes were focused on three main points, namely agricultural products, crop yields, tax-sharing income, while the tax was developed again by economists in Indonesia, income tax (PPN: Pajak Penambahan Nilai), value-added tax (VAT), sales tax on luxury items PPn BM), Customs duty, Land and building tax (PBB), Acquisition fees for land and buildings (BHTB). The essence of tax is a community granting for assets owned for the common welfare.